2018
DOI: 10.25100/cm.v49i4.3919
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, salivary glands and oral pathology

Abstract: Obesity has reached pandemic proportions in recent years. Not only adults suffer from the disease, but increasingly children and young people. One of the main causes of overweight and obesity is excessive food intake, in particular heavily processed carbohydrates. Obesity alters multiple organs, including the salivary glands, bringing functional alterations with it. Among researchers, the relation between obesity and tooth decay, periodontal disease and xerostomia is being debated. More and more scientific rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 71 publications
(174 reference statements)
2
21
0
13
Order By: Relevance
“…Nevertheless, not only tooth decay is a negative consequence of obesity. Chronic gingivitis or periodontitis is one of the most prevalent diseases of an inflammatory-destructive background and, similarly to obesity, it is classified as a social disease [ 18 ]. We found benign gingivitis in both the study and control groups, as shown by the GI and SBI.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, not only tooth decay is a negative consequence of obesity. Chronic gingivitis or periodontitis is one of the most prevalent diseases of an inflammatory-destructive background and, similarly to obesity, it is classified as a social disease [ 18 ]. We found benign gingivitis in both the study and control groups, as shown by the GI and SBI.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and oral health may share similar causal and behavioral mechanisms (8), mainly related to the diet. Previous studies reported an association between obesity and several oral diseases, such as dental caries (9), periodontal disease, tooth loss (7,10,11), and xerostomia (defined as the subjective perception of oral dryness) (9,12).…”
Section: Introductionmentioning
confidence: 99%
“…The latter decreases during weight loss in obese subjects (Rasmusen et al, 1995), which indicates that type III collagen is most affected during obesity, as was found in the stroma of the parotid gland of our experimental model. Type III collagen is composed of immature fibrils, likely due to fibrogenesis or fibrosis of the gland (Karsdal, 2016), which could explain the functional changes in the salivary glands during obesity (Roa & del Sol, 2018).…”
Section: Discussionmentioning
confidence: 99%